Assessing the viscoelastic properties of upper trapezius muscle: Intra- and inter-tester reliability and the effect of shoulder elevation. (December 2018) - Liu, C.L.; Feng, Y.N.; Zhang, H.Q.; Li, Y.P.; Zhu, Y.; Zhang, Z.J.
Abstract: Background: Increasing stiffness in the upper trapezius muscle may contribute to imbalance of scapular motion, and result in shoulder and neck discomfort during shoulder flexion. Therefore, it is essential to quantify upper trapezius stiffness in various shoulder positions in order to aid in the prevention of these disorders and to optimize rehabilitation. Objectives: The objectives of the present study were to examine the intra and inter-tester reliability of MyotonPRO device in measuring upper trapezius stiffness and its ability to determine changes in stiffness during shoulder flexion. Methods: Twenty healthy male subjects (mean age: 28.3 ± 4.8 years) were studied. The stiffness of upper trapezius was quantified using the MyotonPRO device. Results: The results revealed excellent intra and inter-tester reliability for measuring upper trapezius stiffness with the shoulder in a neutral position, and also found a 14.2% increase in stiffness upon shoulder flexion between 0° and 60° of flexion. Minimal detectable change (MDC) was 26.3 N/m. Conclusions: Our findings indicate that MyotonPRO device is a feasible tool to quantify upper trapezius stiffness as well as changes in muscle stiffness. Thus, it is important to assess the changes in upper trapezius muscle stiffness due to pathology or treatments for future studies.